1987
DOI: 10.1203/00006450-198701000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Surfactant Pools in Fetal and Newborn Rat Lungs

Abstract: ABSTRACT. Preparation by the developing alveolar epithelium for the transition to air breathing and surfactant secretion at birth are critical components of neonatal survival. We combined morphometric analysis and biochemical assays of lung phospholipids to measure the amount and redistribution of lung surfactant during the perinatal period of rats. Within 10 min of the start of air breathing, there was a small increase in type I1 cell lamellar body content by morphometric and biochemical estimates. By 24 h, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…volumes and their fractions of respiratory parenchyma were not 3) derives from the relatively small Percentage (10-2 1 %) of total significantly different between control and starved fetuses at d lung DPC that can actually be isolated from purified LB fractions 65 (Table 2). Ultrastructural analyses of type I1 cells indicated of the same lungs (21)(22)(23). The large m~o u n t of non-LB lung no significant interlobar differences for any animal, and data DPC is distributed elsewhere in type 11 cells (including endowere then pooled by animal for intergroup comparisons.…”
Section: Methodsmentioning
confidence: 85%
“…volumes and their fractions of respiratory parenchyma were not 3) derives from the relatively small Percentage (10-2 1 %) of total significantly different between control and starved fetuses at d lung DPC that can actually be isolated from purified LB fractions 65 (Table 2). Ultrastructural analyses of type I1 cells indicated of the same lungs (21)(22)(23). The large m~o u n t of non-LB lung no significant interlobar differences for any animal, and data DPC is distributed elsewhere in type 11 cells (including endowere then pooled by animal for intergroup comparisons.…”
Section: Methodsmentioning
confidence: 85%
“…In the rat, there are increases in alveolar surfactant not associated with a loss of lamellar bodies from type I1 cells that imply complex relationships between intracellular and extracellular pools (12,28,29). Stevens et al (30) demonstrated that, at birth, secretion and surfactant phospholipid reuptake occurred simultaneously, with the net effect being a large increase in the alveolar pool on the first day of life.…”
Section: Resultsmentioning
confidence: 99%
“…There also was no effect of surfactant treatment in that experiment. In term rats, Spain et al [27] reported that alveolar pools increased remarkably after birth, although biochemical or morphometric estimates of lamellar body pool size did not change. Similar morphometric analyses have been published by Faridy et al [28,29].…”
Section: Discussionmentioning
confidence: 99%